FAKTOR YANG BERHUBUNGAN DENGAN TINDAKAN TIDAK AMAN PADA PEKERJA DI PT. PELINDO IV (PERSERO) CABANG KOTA KENDARI - Pitrah Asfian; Uni Zulfiani; Sartiah Yusran (FKM Universitas Halu Oleo, 2021)
Unsafe action is a mistake in understanding and complying with good and correct work procedures. This study aims to find out what factors are related to unsafe acts of workers at PT. Pelindo IV (Persero) Kendari City Branch in 2020. This type of research was a quantitative study with cross sectional approach. The research was conducted from December to January 2021. The sampling technique used a total sampling of 57 field workers. The variables in this study included unsafe actions, knowledge, attitudes, and supervision. The data collection instruments used in this study were questionnaires and documentation in accordance with the needs of the researcher. The data were analyzed using univariate and bivariate analysis with fisher's exact test. Data presentation was done in the form of frequency distribution tables and relationship tables between variables and then narrated. The results shows that 18 or 31.6 workers committed unsafe actions and 39 or 68.4 workers are already in the safe category. There is a relationship of knowledge (p-value = 0.011) and supervision (p-value = 0.022) with unsafe actions. However there is no relationship of attitude (p-value = 0.646) with unsafe actions. The conclusion is that there is no relationship between attitudes and unsafe actions in workers, and there is a relationship between knowledge and supervision and unsafe actions in workers. The Company is expected to provide training or education to workers on the importance of work safety and can improve supervision to workers